Mechanisms of bacterial-to-host interaction and their disorders at inflammatory bowel diseases - Ye. A. Poluektova; O. S. Lyashenko; A. V. Korolev; O. S. Shifrin; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
The aim of review. To discuss modern concepts on interaction of bacterial cells with human body, and disorders of micro-and macroorganism interaction at inflammatory bowel diseases (IBD).Summary. Quantitative and qualitative changes of intestinal microflora are revealed in patients with IBD, with tendency to increase of opportunistic and pathogenic microorganisms contents. The capability of bacteria contact with immune cells is provided by capacity of bacterial cells to adhesion and invasion, competence of mucus layer covering mucosa of gastro-intestinal tract, detaining and fixing microbic cells, competence of intercellular epithelial contacts function, density of signal receptors, level of antimicrobic peptides expression, completeness of autophagy process. Disorder of barrier function of intestine at IBD patients, in combination to prevalence of opportunistic and pathogenic microorganisms in intestinal biome, results in essential overload of innate and adaptive immune system.Conclusion. At IBD, all mechanisms providing interaction of bacterial cells with the host body are malfunc tioning to some extent, that, in combination to genetic predisposition to this disease, results in development of clinical symptoms and morphological changes.